Wage Setting in Times of High and Low Inflation - Maximilian Gödl; Isabel Gödl-Hanisch (CESifo GmbH, 2024)
The recent surge in inflation led many unions and firms to alter their bargaining and wage-setting policies. Using novel German firm-level survey data, we document the extent of state dependence in wage setting across firms and workers during periods of high and low inflation. We find state dependence along the extensive and intensive margins: the average duration of wage agreements shortens from 14.2 to 12.9 months, and the adjustment per pay round increases from 2-4% to 4-6%. We complement these findings with newly compiled union-level panel data on collective bargaining outcomes. We show that the observed state dependence can be rationalized in menu cost and Calvo models of wage setting with heterogeneous firms. We examine the implications of state-dependent wage setting for the long-run effects of trend inflation, the transmission of monetary policy shocks, and the slope of the Phillips curve in an otherwise standard New Keynesian model.
Keywords: E24; E31; E50; E60; 330; state-dependent wage setting; New Keynesian model; heterogeneous firms; Phillips curve